The Influence of the Number of Board of Commissioners, Company Size, Risk Monitoring Committee, and Financial Performance on Earnings Management - Hermanto; Ratna Sari Natalia Berutu (International Journal of Science and Society, 2022)
The purpose of this study is to find determinants of profit management (Earnings Management) such as the number of board of commissioners, the size of the company, the risk monitoring committee, and the financial performance of a company. The current study uses banking sector financial statement data recorded at Bank Indonesia (BI) with selective sampling methods that meet survey criteria. Researchers examined a period of five years using a sample of 120 data from 24 banking sector entities. The study used several methods of linear analysis with secondary data types. This study shows that the size of the board of commissioners, the size of the company, and the risk monitoring committee, and the ROA jointly affect profit management. The size of the board of commissioners and the size of the company individually do not indicate any influence on profit management. Individual risk monitoring committees affect profit management and ROAs individually have a positive influence on profit management.